THE OPTIMAL FREEZING TEMPERATURE OF COW MILK AND CAMEL MILK - UkilimTastemirova; Ravshanbek Alibekov; Inga Ciprovica; Azret Shingisov; Rauan Mukhtarkhanova; Elvira Mailybaeva (Academic Scientific Journal of Chemistry, 2019)
In the freezing process of cow milk and camel milk, three areas of temperature variations were identified. Specifically, on the first period, both types of milk cooled, then supercooled and further the formation process of ice crystals a taken place. On the second area, it was observed the isothermal area and the phase transformation of water into ice was present. On the third stage, the weakly bound water contained in cow milk and camel milk completely transited into ice. Based on a study of the pattern of changes in the amount of frozen moisture, it was found that, at the minis temperature of t=-15 °C, more than 95% of the water consisted in both types of milk are frozen, and further reducing of temperature had monotonously insignificantly increasing behaviour of the freezing. Therefore, from the point of view of energy savings and maximum preservation of the initial qualities during the shelf-life of cow milk and camel milk, the optimal freezing temperature range is recommended.